2017
DOI: 10.1002/adem.201600816
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Properties of the Copper‐Coated SiCp Reinforced Al–Si Alloy Composites

Abstract: Copper-coated silicon carbide (SiC) particles have been developed to improve the strength and wear resistance of Al-Si matrix composites, which are utilized in brake pads and, hence find applications in aerospace and automobile industries. Copper-coated SiC powder is prepared by electroless plating and is characterized by scanning electron microscopy and X-ray diffraction. Copper-coated SiCp reinforced Al-Si composites are prepared by a powder metallurgy method, and their microstructures and properties are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Metal‐encapsulated ceramic particles are commonly fabricated by ball milling, electroless deposition, sol‐gel, and precipitation deposition . Specifically, electroless deposition has been recognized as one of the most useful methods for preparing metal‐encapsulated ceramics . Electroless deposition is an autocatalytic chemical reaction in aqueous solution that can produce the surface metallization of conductive and nonconductive substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐encapsulated ceramic particles are commonly fabricated by ball milling, electroless deposition, sol‐gel, and precipitation deposition . Specifically, electroless deposition has been recognized as one of the most useful methods for preparing metal‐encapsulated ceramics . Electroless deposition is an autocatalytic chemical reaction in aqueous solution that can produce the surface metallization of conductive and nonconductive substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 46 ] found that the surface modification of β-Si 3 N 4 whiskers can improve the relative density of β-Si 3 N 4 w/Al composites. Feng et al [ 47 ] electroless plated Cu on the surface of SiCp, which could greatly improve the wettability of SiCp and Al-Si alloys, and then the density of the composites was greatly improved. These results can be used to further improve the densification results of the material.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from formula (5), for the wetting angle of SiCp and AlSi12 alloy melt, when θ < 90°, ΔP > 0, ΔP promotes the passage of AlSi12 melt. When θ > 90°, ΔP < 0, ΔP hinders the passage of AlSi12 melt.…”
Section: Infiltration Process Analysis Of Alsi12 Alloy Meltmentioning
confidence: 99%
“…SiCp/Al composites are widely used in aerospace, automotive, electronic packaging, and other fields [1][2][3][4][5] due to their high strength, high modulus, and excellent wear resistance. [6][7][8][9] The application demand of SiCp/Al composites with thickness more than 200 mm is increasing.…”
Section: Introductionmentioning
confidence: 99%